Magnetic carrier, two-component developer, and replenishment developer

A magnetic carrier with a polyrotaxane resin layer addresses excessive charging in low-humidity environments by enhancing charge mobility, ensuring consistent image density in electrophotographic devices.

JP7604274B2Active Publication Date: 2024-12-23CANON KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021038670
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-10
Publication Date
2024-12-23
Estimated Expiration
2041-03-10

AI Technical Summary

Technical Problem

Magnetic carriers used in electrophotographic image forming devices experience excessive charging in low-humidity environments, leading to a reduction in image density.

Method used

A magnetic carrier with a resin layer containing polyrotaxane, which includes cyclic molecules with chain molecules and blocking groups to prevent detachment, is developed to enhance charge mobility and reduce excessive charging.

Benefits of technology

The magnetic carrier maintains image density in low-humidity environments by facilitating easier charge escape, thereby preventing excessive charging and maintaining image quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604274000003
    Figure 0007604274000003
  • Figure 0007604274000004
    Figure 0007604274000004
  • Figure 0007604274000001
    Figure 0007604274000001
Patent Text Reader

Abstract

To provide a magnetic carrier which prevents lowering of image density under a low humidity environment.MEANS FOR SOLVING THE PROBLEM: A magnetic carrier contains magnetic core particles, and a resin layer coating a surface of the magnetic core particles. The resin layer contains a resin and polyrotaxane. The polyrotaxane has (i) a plurality of cyclic molecules, and (ii) a chain molecule which is included by rings of the cyclic molecules in a skewered state, wherein (iii) the chain molecule has two or more blocking groups for preventing the cyclic molecules from separating from the chain molecule.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a magnetic carrier, a two-component developer, and a replenishment developer. [Background technology]

[0002] In the developer for electrophotographic image forming apparatuses, a two-component developer is known in which a magnetic carrier and a toner are mixed and triboelectrically charged, an appropriate amount of positive or negative charge is imparted to the toner, and the charge is used as a driving force for development. From the viewpoint of sufficiently charging the toner and developing it on a photoreceptor drum, a magnetic carrier having a coating resin on the surface of the magnetic carrier core particles is widely used in order to sufficiently charge the magnetic carrier, and various studies have also been conducted on the coating resin.

[0003] For example, Patent Document 1 discloses that a magnetic carrier contains a coating resin, and that by adding a specific compound to the coating resin, the carrier has excellent halftone image quality, suppression of white dots, and fine line reproducibility after long-term continuous image formation and after being left unused. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-170216 A [Patent Document 2] WO01 / 083566 [Patent Document 3] JP 2017-31258 A [Non-patent literature]

[0005] [Non-Patent Document 1] polym.Eng.Sci., 14(2), 147-154(1974) Summary of the Invention [Problem to be solved by the invention]

[0006] One aspect of the present disclosure is to provide a magnetic carrier that is less likely to reduce image density in a low-humidity environment.

[0007] Another aspect of the present disclosure is directed to providing a two-component developer having the magnetic carrier according to the present disclosure.

[0008] Another aspect of the present disclosure is directed to providing a refill developer having a magnetic carrier according to the present disclosure. [Means for solving the problem]

[0009] According to one aspect of the present disclosure, there is provided a magnetic carrier having a magnetic core particle and a resin layer covering the surface of the magnetic core particle, the resin layer contains a resin and a polyrotaxane, The polyrotaxane is (i) a plurality of cyclic molecules; (ii) a chain molecule that is pierced and included in the ring of the cyclic molecule; having (iii) the chain molecule has two or more blocking groups that prevent the cyclic molecule from being detached from the chain molecule; The magnetic carrier is characterized by the above.

[0010] According to another aspect of the present disclosure, there is provided a two-component developer containing a toner and a magnetic carrier, The magnetic carrier is the magnetic carrier according to the present disclosure. The present invention provides a two-component developer comprising:

[0011] According to another aspect of the present disclosure, there is provided a replenishment developer containing a toner and a magnetic carrier, comprising: The magnetic carrier is the magnetic carrier according to the present disclosure. A replenishing developer comprising: Effect of the Invention

[0012] According to one aspect of the present invention, it is possible to provide a magnetic carrier that is less likely to reduce image density in a low humidity environment. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic diagram showing one embodiment of a cross section of a magnetic carrier according to the present disclosure. [Diagram 2] FIG. 2 is a schematic diagram of a resistivity measuring device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] In the present invention, the expressions "xx or more and xx or less" and "xx to xx" expressing a numerical range mean a numerical range including the lower and upper limit endpoints, unless otherwise specified.

[0015] <Background to the invention> In recent years, image forming apparatuses are required to be less susceptible to image defects even in harsh environments. One example of such image defects is a phenomenon in which the density of a formed image is likely to decrease due to excessive charging of toner or magnetic carrier, particularly in a low humidity environment. Various studies have been conducted on this decrease in image density, but the present inventors believe that there is still room for improvement.

[0016] The present inventors focused on the excessive charging of the magnetic carrier in a low-humidity environment and considered that it was necessary to consider ways to reduce the excessive charging of the magnetic carrier by improving the coating resin layer, which is a configuration that is widely used for magnetic carriers, and thereby to make it less likely that a decrease in image density will occur in a low-humidity environment.

[0017] Based on the above-mentioned idea, the present inventors have investigated magnetic carriers having resin layers containing various materials in order to obtain a magnetic carrier that is less likely to reduce image density in a low-humidity environment, and have found that a carrier having a resin layer containing polyrotaxane is effective in realizing a carrier having the above-mentioned characteristics.

[0018] Since the cyclic molecules contained in the polyrotaxane can rotate and move along the chain molecules, the polyrotaxane is a material with high molecular mobility. The present inventors believe that by incorporating such a material with high molecular mobility into the resin layer on the surface of the magnetic carrier, the charge generated in the resin layer can be easily moved, and this makes it easier to release excess charge generated in the magnetic carrier. As a result, the present inventors speculate that the magnetic carrier is less likely to be excessively charged even in a low humidity environment, and image density is less likely to decrease.

[0019] <Polyrotaxane> The coating resin layer according to the present disclosure contains a polyrotaxane having (i) a plurality of cyclic molecules, (ii) linear molecules that are skewered and included in the rings of the cyclic molecules, and (iii) the linear molecules have two or more blocking groups that prevent the cyclic molecules from being detached from the linear molecules.

[0020] Generally, a molecular assembly in which a chain molecule penetrates the inside of the ring of a cyclic molecule and bulky molecules are attached to both ends of the axis to bind the cyclic molecule to the chain molecule is called a rotaxane. A molecular assembly in which many cyclic molecules are linked to one chain molecule is called a polyrotaxane. The cyclic molecule is not bound to the chain molecule and can rotate and move on the chain molecule.

[0021] From the viewpoint of developability, the content of polyrotaxane relative to the mass of the coating resin is preferably 0.2% by mass or more and 30.0% by mass or less. The lower limit of the content is more preferably 0.5% by mass or more. The upper limit of the content is more preferably 15.0% by mass or less, and even more preferably 10.0% by mass or less.

[0022] The polyrotaxane of the present disclosure can be produced by a publicly known method, for example, the method described in Patent Document 2 or Patent Document 3, or can be obtained and used as a commercially available product (product name: CELME Super Polymer, manufactured by ASM).

[0023] In the polyrotaxane of the present disclosure, the number of cyclic molecules threaded by one linear molecule (the inclusion amount) is not particularly limited. The inclusion amount can be controlled by the molar ratio of the linear molecule and the cyclic molecule used in producing the polyrotaxane.

[0024] <Bonded polyrotaxane> The cyclic molecules of the two or more polyrotaxanes may have a structure in which they are chemically bonded via a single bond or a linking group.

[0025] That is, the resin layer contains a bound polyrotaxane formed by binding a first polyrotaxane to a second polyrotaxane, The first polyrotaxane and the second polyrotaxane may be bonded to each other by forming a chemical bond between a cyclic molecule contained in the first polyrotaxane and a cyclic molecule contained in the second polyrotaxane.

[0026] Furthermore, one polyrotaxane may have a structure in which a plurality of cyclic molecules are bonded to each other via a single bond or a linking group.

[0027] In the present disclosure, a chemical bond may be a single bond or a bond via various atoms or molecules (eg, a bond via a linking group).

[0028] <Cyclic molecules> The cyclic molecules contained in the polyrotaxane are not particularly limited as long as they are capable of including chain molecules and have a ring structure through which the chain molecules can penetrate in a skewered manner.

[0029] Examples of the cyclic molecule of the present disclosure include cyclodextrins, crown ethers, benzocrowns, dibenzocrowns, dicyclohexanocrowns, and derivatives or modified forms thereof. Among these, cyclodextrins are preferred because they are easy to include chain molecules. That is, the cyclic molecule is preferably a molecule having a cyclodextrin skeleton. More preferably, the cyclic molecule is a molecule having at least one cyclodextrin skeleton selected from the group consisting of an α-cyclodextrin skeleton, a β-cyclodextrin skeleton, and a γ-cyclodextrin skeleton. The cyclic molecule may be one type, or two or more types may be used in combination.

[0030] In the present disclosure, a molecule having a cyclodextrin skeleton is considered to be a molecule having a structure that is synthesized when a derivatization reaction is performed on a hydroxy group of a cyclodextrin molecule and / or a cyclodextrin compound.

[0031] <Side chains attached to cyclodextrin> It is preferable that the cyclic molecule of the polyrotaxane is a molecule having a cyclodextrin skeleton, and the molecule having the cyclodextrin skeleton has cyclodextrin and a side chain bonded to the cyclodextrin. Here, the side chain bonded to the cyclodextrin in the present disclosure is treated as a partial structure introduced when a derivatization reaction is performed on a hydroxy group of the cyclodextrin. The side chain may be a linear structure or a branched structure.

[0032] It is believed that the above-mentioned side chains tend to increase the affinity between the polyrotaxane and the resin. As a result, it is believed that the polyrotaxane is likely to be contained in the resin layer in a uniformly dispersed state, which is preferable. In addition, it is more preferable that the side chains have a polymer structure, and more preferably a polyester structure or a vinyl polymer structure. Examples of the polyester structure include a polymer structure in which a diol and a dicarboxylic acid are condensed, and a polycaprolactone structure. In addition, the vinyl polymer structure is a polymer structure in which a vinyl monomer is polymerized, and examples thereof include a styrene-methyl methacrylate polymer structure.

[0033] In addition, the weight average molecular weight of the molecule having the above-mentioned side chain and the cyclodextrin skeleton is preferably 1000 to 50000. It has been found that image fogging is less likely to occur in a high-temperature and high-humidity environment when the weight average molecular weight is 1000 or more. The inventors believe that the reason image fogging is less likely to occur is that the polyrotaxane and the resin are entangled, and the self-repairing function of the polyrotaxane makes the resin layer more excellent in scratch resistance, making it difficult for the magnetic particles to be exposed. Therefore, it is preferable that the molecular weight is 1000 or more, more preferably 2500 or more, and even more preferably 7000 or more. It has also been found that the molecular weight is 50000 or less, which makes it difficult for the molecular mobility of the cyclic molecules to become too small, and it is thought that the excess charge in the magnetic carrier can be sufficiently released, making it difficult for the image density to decrease. Therefore, it is preferable that the molecular weight is 50000 or less, more preferably 20000 or less, and even more preferably 10000 or less.

[0034] A molecule having a cyclodextrin skeleton that satisfies the above weight-average molecular weight can be produced, for example, by bonding a polymer structure to cyclodextrin. For example, it can be produced by introducing a polyester structure into the hydroxyl group of cyclodextrin. It can also be produced by a vinyl polymerization reaction between a cyclodextrin derivative having a vinyl-polymerizable double bond and a vinyl monomer.

[0035] The molecular weight of the cyclic molecules in the polyrotaxane can be measured by an analytical device such as GPC after isolating the cyclic molecules. In order to isolate the cyclic molecules, the terminal blocking groups of the polyrotaxane must be removed as a first step. For example, in the case of polyrotaxanes having terminal blocking groups bonded with amide groups or carbonyl groups, a method of heating under acid or base conditions to cause hydrolysis can be used. The cyclic molecules can then be isolated by conventional methods such as reprecipitation, filtration, centrifugation, and membrane separation.

[0036] <chain molecule> The chain molecule of the polyrotaxane is not particularly limited as long as it can pierce the cyclic molecule in a skewered manner, is included in the cyclic molecule, and allows the cyclic molecule to freely rotate, slide, or move. The length of the straight chain is also not particularly limited. A straight chain molecule is preferable. In the present disclosure, a straight chain molecule is considered to be a molecule having no branch in the main chain of the molecule.

[0037] The chain molecule is preferably at least one selected from the group consisting of polyalkylenes, polyesters, polyethers, polyamides, and polyacrylics, and among these, polyethers are more preferable. That is, the chain molecule is preferably a molecule having a polyether chain. More preferably, it is a molecule having a polyalkylene glycol chain, and even more preferably, it is a molecule having a polyethylene glycol chain.

[0038] <Blocking group> The chain molecule has two or more blocking groups at its terminals to prevent the cyclic molecules from being released. The blocking groups of the polyrotaxane can be used without any particular limitation as long as they have a structure that can prevent the cyclic molecules from being released. Examples of the blocking groups according to the present disclosure include bulky groups that physically prevent the cyclic molecules from being released, and ionic groups that electrically prevent the cyclic molecules from being released. Specific examples include dinitrophenyl groups, adamantyl groups, trityl groups, and pyrenyl groups. Specific examples include cyclodextrins and fluoresceins that are introduced as substituents at the terminals of the chain molecules. The blocking groups may also be derivatives or modified forms of the above.

[0039] <Resin layer> The resin layer of the present disclosure contains a resin. The resin may be a thermosetting resin, but is preferably a thermoplastic resin because it is considered that the mobility of the cyclic molecules described above is less likely to be hindered. In addition, the resin layer preferably contains at least one resin selected from the group consisting of acrylic resin, polyester, silicone resin, and fluororesin. Furthermore, the sum of the mass of the at least one resin selected from the group is preferably 50% by mass or more with respect to the total mass of the resin contained in the resin layer.

[0040] In addition to the above, examples of thermoplastic resins include the following: polystyrene, polymethyl methacrylate, styrene-acrylic acid ester copolymer, styrene-methacrylic acid ester copolymer, styrene-butadiene copolymer, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinyl acetate, polyvinylidene fluoride resin, fluorocarbon resin, perfluorocarbon resin, solvent-soluble perfluorocarbon resin, polyvinylpyrrolidone, petroleum resin, novolac resin, saturated alkyl polyester resin, aromatic polyester resin such as polyethylene terephthalate, polybutylene terephthalate, and polyarylate, polyamide resin, polyacetal resin, polycarbonate resin, polyethersulfone resin, polysulfone resin, polyphenylene sulfide resin, and polyether ketone resin.

[0041] Examples of the thermosetting resin include the following: Phenolic resins, modified phenolic resins, maleic resins, alkyd resins, epoxy resins, acrylic resins, unsaturated polyesters obtained by polycondensation of maleic anhydride, terephthalic acid and polyhydric alcohols, urea resins, melamine resins, urea-melamine resins, xylene resins, toluene resins, guanamine resins, melamine-guanamine resins, acetoguanamine resins, glyptal resins, furan resins, silicone resins, polyimides, polyamide-imide resins, polyetherimide resins and polyurethane resins.

[0042] The ratio of the mass of the resin to the mass of the magnetic core particles is preferably 1.0 to 5.0% by mass.

[0043] In the present disclosure, the resin layer means all the resin layers that cover the magnetic core particles. That is, as shown in Fig. 1, the resin layer 2 that covers the magnetic core particle 1 may be composed of multiple resin layers (for example, when there are two layers, it may be composed of the resin layer 3 and the resin layer 4).

[0044] <Resin A> It is preferable that the resin layer contains resin A, the ratio of the mass of resin A to the total mass of the resins contained in the resin layer is 50 mass % or more, and resin A satisfies the following relationship: That is, the SP value of resin A is SPa (J / cm 3 ) 1 / 2 The SP value of the side chain in the molecule having the above-mentioned cyclodextrin skeleton is SPb (J / cm 3 ) 1 / 2 When set at , it is preferable to satisfy the following formula (1). |SPb-SPa|≦2.0(J / cm 3 ) 1 / 2 ... (1) The SP value is calculated by the following formula (2). SP value (J / cm 3 ) 1 / 2 =√(Ev / v)=√(ΣΔei / ΣΔvi) ··· (2) (The abbreviations in formula (2) are as follows: Ev: Evaporation energy (J / mol), v: molar volume (cm 3 / mol), Δei: evaporation energy of each atom or group of atoms, Δvi: the molar volume of each atom or group of atoms)

[0045] The SP value of resin A can be calculated by calculating the SP value of each of the monomer units constituting resin A, multiplying them by the mol% in resin A, and adding them up. For example, when resin A is composed of a single monomer unit, the SP value of the monomer unit is regarded as the SP value of resin A itself. When resin A is composed of two types of monomer units (50:50 molar ratio), the SP values ​​of the two types of monomer units are calculated, and their average value is regarded as the SP value of resin A. Similarly, when the side chain has a polymer portion, the SP value of the side chain is calculated using the monomer units constituting the polymer portion and their molar ratio.

[0046] By satisfying the above formula (1), it is considered that the compatibility between the polyrotaxane and the resin is easily increased, and the polyrotaxane is easily contained in a dispersed state in the resin layer, which is preferable.

[0047] In addition, for the evaporation energy and molar volume in the above formula (2), the values ​​in the table described in Non-Patent Document 1 are used.

[0048] The resin A is preferably an acrylic resin, a polyester resin, a fluororesin, or a silicone resin, and more preferably an acrylic resin or a polyester resin.

[0049] <Magnetic core particles> As the magnetic core particles according to the present disclosure, known magnetic particles such as magnetite particles, ferrite particles, and magnetic material-dispersed resin particles can be used.

[0050] The volume average particle diameter (D50) of the magnetic core particles is preferably 20 μm or more and 80 μm or less in order to uniformly coat the resin, prevent carrier adhesion, and appropriately adjust the density of the developer magnetic brush to obtain a high-quality image, and more preferably 20 μm or more and 50 μm or less.

[0051] The resistivity of the magnetic core particles is 1.0×10 5 (Ω cm) or more 1.0×10 14 If the resistivity is less than 1.0×10 10 The specific resistance can be controlled by the type of magnetic material, the amount of magnetization in the case of porous magnetic core particles, the amount of filled resin, and the like.

[0052] The method of coating the surface of the magnetic core particles with resin is not particularly limited, and can be performed by a known method. For example, there is a so-called immersion method in which the carrier core and the resin solution are stirred while the solvent is evaporated, and the resin is coated on the surface of the carrier core. Specific examples of the device for stirring include a universal mixer (manufactured by Fuji Paudal Co., Ltd.) and a Nauta mixer (manufactured by Hosokawa Micron Co., Ltd.).

[0053] In addition, there is a method in which a coating resin solution is sprayed from a spray nozzle while forming a fluidized bed, and the surfaces of the magnetic core particles are coated with the resin. Specific examples of the apparatus used include Spiracoater (manufactured by Okada Seiko Co., Ltd.) and Spiraflow (manufactured by Freund Corporation).

[0054] There is also a method of coating the magnetic carrier core with a coating resin in a particle state by a dry method.Specific examples of such methods include a treatment method using a device such as Hybridizer (manufactured by Nara Machinery Works), Mechanofusion (manufactured by Hosokawa Micron Corporation), Hyflex Gral (manufactured by Fukae Powtec), or Theta Composer (manufactured by Tokuju Machinery Works).

[0055] <Two-component developer and replenishment developer> The magnetic carrier according to the present disclosure is preferably used as a two-component developer. That is, a preferred embodiment of the present disclosure is a two-component developer containing a toner and a magnetic carrier, and the magnetic carrier is preferably the magnetic carrier according to the present disclosure. The two-component developer is a developer for developing an electrostatic latent image formed on an electrostatic latent image carrier.

[0056] Similarly, the magnetic carrier according to the present disclosure is preferably used as a refill developer. That is, as a preferred embodiment of the present disclosure, a refill developer containing a toner and a magnetic carrier is preferably the magnetic carrier according to the present disclosure. The refill developer is a developer for refilling a developing device in response to a decrease in the toner concentration in the two-component developer in the developing device.

[0057] <Toner> The toner in the present disclosure is preferably a toner having toner particles. A preferred toner configuration will be described below.

[0058] <Binding resin> The toner particles of the present disclosure preferably contain a binder resin. Examples of the binder resin include the following resins. Homopolymers of styrene and its substituted derivatives, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; Styrenic copolymers such as styrene-p-chlorostyrene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-acrylic acid ester copolymer, styrene-methacrylic acid ester copolymer, styrene-α-chloromethyl methacrylate copolymer, styrene-acrylonitrile copolymer, styrene-vinyl methyl ether copolymer, styrene-vinyl ethyl ether copolymer, styrene-vinyl methyl ketone copolymer, and styrene-acrylonitrile-indene copolymer; Polyvinyl chloride, phenolic resin, natural modified phenolic resin, natural resin modified maleic acid resin, acrylic resin, methacrylic resin, polyvinyl acetate, silicone resin, polyester, polyurethane, polyamide, furan resin, epoxy resin, xylene resin, polyvinyl butyral, terpene resin, coumarone-indene resin, petroleum-based resin.

[0059] Among these, it is preferable to use polyester from the viewpoint of low-temperature fixability and chargeability of the toner.

[0060] If necessary, the toner may contain one or more additives selected from colorants, waxes, charge control agents, inorganic fine particles, etc. Various additives used in the toner will be specifically described.

[0061] <Wax> Examples of waxes include the following: Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax. Oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof. Waxes whose main component is fatty acid esters such as carnauba wax. Partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax.

[0062] Among these, from the viewpoints of low-temperature fixing property and hot offset resistance of the toner, hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax are preferred. In the present disclosure, from the viewpoint of hot offset resistance of the toner, hydrocarbon waxes are more preferred.

[0063] The content of the wax in the toner particles is preferably 1.0 part by mass or more and 20.0 parts by mass or less with respect to 100 parts by mass of the binder resin.

[0064] From the viewpoint of the storage stability and hot offset resistance of the toner, it is preferable that the peak temperature of the endothermic peak derived from the wax in the endothermic curve during temperature rise measured by a differential scanning calorimeter (DSC) using the toner as a measurement sample is 50°C or higher and 110°C or lower.

[0065] <Coloring agent> Examples of the colorant include the following: As the colorant, a pigment may be used alone, or a dye and a pigment may be used in combination.

[0066] Carbon black as a black colorant; a yellow colorant, a magenta colorant, and a cyan colorant were used to adjust the black color.

[0067] Examples of color pigments for magenta toner include the following: Condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specifically, CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 144, 146, 150, 163, 166, 169, 177, 184, 185, 202, 206, 207, 209, 220, 221, 238, 254, 269; CI Pigment Violet 19, CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.

[0068] Dyes for magenta toner include the following: Solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121, CI Disperse Red 9, CI Solvent Violet 8, 13, 14, 21, 27, CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40, CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.

[0069] Examples of color pigments for cyan toner include the following: CI Pigment Blue 1, 2, 3, 7, 15:2, 15:3, 15:4, 16, 17, 60, 62, 66; CI Bat Blue 6, CI Acid Blue 45, copper phthalocyanine pigments with 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton.

[0070] Yellow color pigments include the following: Condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal compounds, methine compounds, and allylamide compounds. Specifically, CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 155, 168, 174, 180, 181, 185, 191; CI Bat Yellow 1, 3, 20. In addition, dyes such as CI Direct Green 6, CI Basic Green 4, CI Basic Green 6, and Solvent Yellow 162 can also be used.

[0071] The content of the colorant in the toner particles is preferably 0.1 parts by mass or more and 30.0 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles.

[0072] <Magnetic material> The toner of the present disclosure may be either a magnetic toner or a non-magnetic toner, but when used as a magnetic toner, it is preferable to use magnetic iron oxide as the magnetic material contained in the toner particles. Examples of magnetic iron oxide include magnetite, maghematite, and ferrite.

[0073] The content of the magnetic material in the toner particles is preferably 25 parts by mass or more and 95 parts by mass or less, and more preferably 30 parts by mass or more and 45 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0074] <Charge control agent> The toner of the present disclosure may contain a charge control agent. The charge control agent may be a negative charge control agent or a positive charge control agent.

[0075] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes.

[0076] When the toner contains a charge control agent, the charge control agent may be added internally or externally to the toner particles.

[0077] The content of the charge control agent in the toner is preferably 0.2 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles.

[0078] <External additives> The toner of the present disclosure may contain an external additive in order to improve the fluidity of the toner or adjust the triboelectric charge amount. As the inorganic particulate external additive, inorganic particulates such as silicon oxide (silica), aluminum oxide (alumina), titanium oxide (titania), strontium titanate, and calcium carbonate are preferred. As the external additive other than inorganic particulates, for example, resin particulates such as vinyl resin, polyester, and silicone resin can be mentioned.

[0079] These inorganic fine particles and resin fine particles function as assistants for controlling the chargeability of the toner and for improving fluidity and cleaning.

[0080] <Method of manufacturing toner particles> The toner particles of the present disclosure can be produced by a known method for producing toner particles, such as a melt kneading method, an emulsion aggregation method, or a solution suspension method.

[0081] The procedure for producing the toner by the pulverization method will be described below. In the raw material mixing process, materials constituting the toner particles, such as binder resin, release agent, colorant, crystalline polyester, and other components such as charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include double con mixers, V-type mixers, drum mixers, super mixers, Henschel mixers, Nauta mixers, and Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.).

[0082] Next, the mixed materials are melt-kneaded to disperse the wax in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of continuous production. For example, a KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with a two-roller or the like, and cooled with water or the like in a cooling process.

[0083] The cooled resin composition is then pulverized to a desired particle size in a pulverization process, which involves coarse pulverization using a pulverizer such as a crusher, hammer mill, or feather mill, followed by further pulverization using a pulverizer such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type pulverizer.

[0084] Thereafter, as necessary, the mixture is classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation).

[0085] Examples of methods for external addition include a method of stirring and mixing using a mixing device such as a double con mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation) as an external addition device. In this case, external additives other than silica fine particles, such as a fluidizing agent, may be added as necessary.

[0086] <Various measurement methods> <Measurement of weight average particle size (D4) of toner particles> The weight-average particle diameter (D4) of the toner particles is measured with an effective measurement channel count of 25,000 channels using a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software for setting measurement conditions and analyzing measurement data, "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), and the measurement data is analyzed and calculated.

[0087] The aqueous electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in deionized water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter).

[0088] Before performing measurements and analysis, the dedicated software is set up as follows.

[0089] In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement.

[0090] In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.

[0091] The specific measurement methods are as follows (1) to (7).

[0092] (1) Pour about 200 ml of the above electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture Tube Flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube.

[0093] (2) Place about 30 ml of the above electrolyte solution in a 100 ml flat-bottom glass beaker, and add about 0.3 ml of a solution prepared by diluting "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments made from a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) three times by mass with deionized water as a dispersant.

[0094] (3) A specified amount of deionized water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 ml of the above-mentioned Conaminon N is added to this water tank.

[0095] (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized.

[0096] (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner particles are added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower.

[0097] (6) In the round-bottom beaker (1) placed in the sample stand, the electrolyte solution (5) in which the toner particles are dispersed is dropped using a pipette to adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000.

[0098] (7) Analyze the measurement data using the dedicated software that comes with the device and calculate the weight-average particle size (D4). Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4).

[0099] <Measurement of the volume average particle size (D50) of magnetic core particles> For the measurement of the volume average particle diameter (D50), it is carried out by attaching a sample feeder for dry measurement, "One Shot Dry Type Sample Conditioner Turbotrac" (manufactured by Nikkiso Co., Ltd.). The control is automatically performed on software. The particle diameter is the 50% particle diameter (D50) which is the cumulative value of the volume average. The control and analysis are performed using the attached software (version 10.3.3 - 202D). The measurement conditions are as follows. · SetZero time: 10 seconds · Measurement time: 10 seconds · Number of measurements: 1 time · Particle refractive index: 1.81% · Particle shape: non - spherical · Measurement upper limit: 1408μm · Measurement lower limit: 0.243μm · Measurement environment: 23℃, 50%RH

[0100] <Measurement of weight - average molecular weight by GPC> The molecular weight distribution of the sample is measured by gel permeation chromatography (GPC) as follows.

[0101] First, dissolve the sample in tetrahydrofuran (THF) over 24 hours at room temperature. Then, filter the obtained solution through a solvent - resistant membrane filter "Mae Sho Ridi Disk" (manufactured by Tosoh Corporation) with a pore size of 0.2μm to obtain a sample solution. Note that the sample solution is adjusted so that the concentration of the components soluble in THF is about 0.8 mass%. Using this sample solution, the measurement is carried out under the following conditions. · Apparatus: HLC8120 GPC (Detector: RI) (manufactured by Tosoh Corporation) · Column: 7 - series of Shodex KF - 801, 802, 803, 804, 805, 806, 807 (manufactured by Showa Denko KK) · Eluent: Tetrahydrofuran (THF) · Flow rate: 1.0ml / min · Oven temperature: 40.0℃ · Sample injection volume: 0.10ml In calculating the molecular weight of a sample, a molecular weight calibration curve prepared using standard polystyrene resins (e.g., trade names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation) is used.

[0102] <Measurement of resistivity value> The resistivity of the sample is measured using a measuring device as shown in Fig. 2. The resistivity is measured at an electric field strength of 2000 (V / cm).

[0103] Resistance measurement cell A has a cross-sectional area of ​​2.4 cm 2 It is composed of a cylindrical container (made of PTFE resin) 17 with a hole, a lower electrode (made of stainless steel) 18, a support base (made of PTFE resin) 19, and an upper electrode (made of stainless steel) 20. The cylindrical container 18 is placed on the support base 19, and a powdered sample 21 is filled to a thickness of about 1 mm. The upper electrode 20 is placed on the filled sample 21, and the thickness of the sample is measured. As shown in Figure 2(a), the gap when there is no sample is d1, and as shown in Figure 2(b), the gap when the sample is filled to a thickness of about 1 mm is d2. The thickness d of the sample is calculated by the following formula. d = d2 - d1 (mm)

[0104] At this time, the mass of the sample is appropriately changed so that the thickness d of the sample is 0.95 mm or more and 1.04 mm or less.

[0105] The resistivity of the sample can be obtained by applying a DC voltage between the electrodes and measuring the current that flows at that time. For the measurement, an electrometer 22 (Kessley 6517A, manufactured by Kessley) and a processing computer 23 for control are used. A control system and control software (LabVEIW, manufactured by National Instruments) manufactured by National Instruments are used for the processing computer for control.

[0106] The measurement conditions were: contact area between the sample and the electrode S = 2.4 cm 2The measured value d is input so that the thickness of the sample is 0.95 mm or more and 1.04 mm or less. The load on the upper electrode is 270 g, and the maximum applied voltage is 1000 V. Resistivity (Ω cm) = (applied voltage (V) / measured current (A)) × S (cm 2 ) / d(cm) Electric field strength (V / cm) = applied voltage (V) / d (cm) The resistivity values ​​of the magnetic carrier and the porous magnetic core at an electric field strength of 2000 (V / cm) are read from a graph in which the resistivity value is plotted on the vertical axis and the electric field strength is plotted on the horizontal axis. EXAMPLES

[0107] The present invention will be described in more detail below with reference to examples, but is not limited thereto. First, the preparation of various polyrotaxanes and coating resins used in the examples, and examples of the production of magnetic core particles will be described.

[0108] <Toner 1 Manufacturing Example> Polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane: 100.0 mol% Terephthalic acid: 80.0 mol% based on the total number of moles of polycarboxylic acids Trimellitic anhydride: 20.0 mol% based on the total number of moles of polycarboxylic acids The monomer material was put into a reaction vessel equipped with a cooling pipe, a stirrer, a nitrogen inlet pipe, and a thermocouple. Then, 1.5 parts by mass of tin 2-ethylhexanoate was added as a catalyst (esterification catalyst) to 100 parts by mass of the total amount of the monomer material. Next, the inside of the reaction vessel was replaced with nitrogen gas, and the temperature was gradually raised while stirring, and the reaction was carried out for 2 hours while stirring at a temperature of 200°C.

[0109] Furthermore, the pressure in the reaction tank was reduced to 8.3 kPa and maintained for 1 hour, and then the pressure was cooled to 180°C and the reaction was continued. After confirming that the softening point measured in accordance with ASTM D36-86 reached 122°C, the temperature was reduced to stop the reaction, and Polyester 1 was obtained.

[0110] The resulting polyester 1 had a softening point (Tm) of 112°C and a glass transition temperature (Tg) of 63°C. Polyester 1 100.0 parts by weight 0.1 parts by weight of 3,5-di-t-butylsalicylic acid aluminum compound Fischer-Tropsch wax (peak temperature of maximum endothermic peak in DSC measurement: 90°C) 5.0 parts by mass CI Pigment Blue 15:3 5.0 parts by weight

[0111] Next, the above materials were mixed in a Henschel mixer (product name: FM75J type, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 20 s -1 After mixing under conditions of 1000 and 5 minutes of rotation time, the mixture was kneaded in a twin-screw kneader (product name: PCM-30, manufactured by Ikegai Corporation) set at a temperature of 125°C. The kneaded mixture was cooled and coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. The coarsely crushed product was finely crushed using a mechanical crusher (product name: T-250, manufactured by Turbo Kogyo Co., Ltd.). Further, classification was performed using a rotary classifier (product name: 200TSP, manufactured by Hosokawa Micron Corporation) to obtain toner particles. The operating conditions of the rotary classifier (product name: 200TSP, manufactured by Hosokawa Micron Corporation) were a classification rotor rotation speed of 50.0 s -1 It was decided.

[0112] The weight average particle size (D4) of the obtained toner particles was 6.2 μm.

[0113] To 100.0 parts by mass of the obtained toner particles, 1.0 parts by mass of hydrophobic silica fine particles having a primary average particle size of 15 nm and surface-treated with 20.0% by mass of hexamethyldisilazane were added. They were mixed in a Henschel mixer (product name: FM75J type, manufactured by Nippon Coke & Engineering Co., Ltd.) and passed through an ultrasonic vibration sieve with an opening of 54 μm to obtain toner 1.

[0114] <Manufacturing example of magnetic core particles> Process 1 (weighing and mixing process) The following ferrite raw materials were weighed and prepared. Fe2O361.7 parts by mass MnCO334.2 parts by mass Mg(OH)23.0 parts by mass SrCO31.1 parts by mass

[0115] These were ground and mixed for 2 hours in a dry ball mill using zirconia balls (φ10 mm).

[0116] Step 2 (pre-firing step) After crushing and mixing, the mixture was sintered in air at 950°C for 2 hours in a burner-type sintering furnace to produce calcined ferrite. The composition of the ferrite is as follows: (MnO)a(MgO)b(SrO)c(Fe2O3)d In the above formula, a = 0.40, b = 0.07, c = 0.01, d = 0.52

[0117] Process 3 (Crushing process) After crushing to about 0.5 mm with a crusher, 30 parts by mass of water was added to 100 parts by mass of the calcined ferrite and crushed in a wet ball mill using zirconia balls (φ1.0 mm) for 2 hours. After separating the balls, the mixture was crushed in a wet bead mill using zirconia beads (φ1.0 mm) for 3 hours to obtain a ferrite slurry.

[0118] Process 4 (granulation process) To the ferrite slurry, 2.0 parts by mass of polyvinyl alcohol was added as a binder relative to 100 parts by mass of the calcined ferrite, and the mixture was granulated into spherical particles of 40 μm using a spray dryer (manufactured by Okawara Kakoki Co., Ltd.).

[0119] Step 5 (Main firing step) In order to control the firing atmosphere, firing was performed in an electric furnace under a nitrogen atmosphere (oxygen concentration 1.0% by volume) at a temperature of 1150° C. for 4 hours.

[0120] Step 6 (sorting step) The aggregated particles were crushed and then sieved through a sieve with 250 μm openings to remove coarse particles, obtaining porous magnetic particles. The volume average particle size (D50) of the magnetic particles was 38 μm and the specific resistance was 4.0×107 The value was Ω·cm.

[0121] Process 7 (resin filling process) 100.0 parts by mass of the above magnetic particles were placed in the stirring vessel of a mixer (product name: Universal Stirrer NDMV type, manufactured by Dalton), and nitrogen was introduced while reducing the pressure to 2.3 kPa while maintaining the temperature at 60° C. Furthermore, a silicone resin solution was added dropwise under reduced pressure so that the resin component was 7.5 parts by mass relative to the magnetic particles, and stirring was continued for 2 hours after the end of the dropwise addition.

[0122] Thereafter, the temperature was raised to 70° C., the solvent was removed under reduced pressure, and the silicone resin composition contained in the silicone resin solution was filled into the porous magnetic particles to obtain filled core particles.

[0123] After cooling, the filled core particles obtained above were transferred to a mixer (product name: Drum Mixer UD-AT type, manufactured by Sugiyama Heavy Industries Co., Ltd.) equipped with a spiral blade in a rotatable mixing container, and the temperature was raised to 220°C at a heating rate of 2 (°C / min) under normal pressure in a nitrogen atmosphere. The mixture was further heated and stirred at 220°C for 60 minutes to harden the resin.

[0124] After the heat treatment, the low magnetic particles were separated by magnetic separation and classified using a sieve with an opening of 150 μm to obtain magnetic core particles. The volume average particle size (D50) of the magnetic core particles was 40 μm and the specific resistance value was 4.4×10 7 The value was Ω·cm.

[0125] <Preparation of polyrotaxane B1> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred. 10.0g of the following polyrotaxane 1 (Polyrotaxane 1: SeRM Super Polymer SA1305P-20 (product name), manufactured by ASM. The chain molecule has a polyethylene glycol structure and an adamantyl group at the end of the chain molecule, and contains, as a cyclic molecule, multiple α-cyclodextrins having a polycaprolactone structure in the side chain. In addition, since the end of the side chain has an acrylic skeleton, it has a vinyl polymerizable carbon-carbon double bond.) 40mL of 1.0N NaOH solution 1,4-Butanediol diglycidyl ether (Tokyo Chemical Industry Co., Ltd.) 1.2 mL

[0126] The mixture was stirred at 23°C for 24 hours to obtain a polyrotaxane in which cyclodextrins were crosslinked. After isolation, 600.0g of xylene, 150.0g of styrene, 50.0g of methyl methacrylate, and 1.5g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 3 hours while rotating the stirrer and maintaining the temperature at 90°C to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane B1 in which cyclodextrins were chemically bonded to each other and side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure were bonded to the cyclodextrins.

[0127] <Preparation of Polyrotaxane B2> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred. 10.0g of the following polyrotaxane 2 (Polyrotaxane 2: SeRM Super Polymer SM1305P-20 (product name), manufactured by ASM. The chain molecule has a polyethylene glycol structure and an adamantyl group at the end of the chain molecule, and contains, as a cyclic molecule, multiple α-cyclodextrins having a polycaprolactone structure in the side chain. In addition, since the end of the side chain has a methacryl skeleton, it has a vinyl polymerizable carbon-carbon double bond.) 40mL of 1.0N NaOH solution 1,4-Butanediol diglycidyl ether (Tokyo Chemical Industry Co., Ltd.) 1.2 mL The mixture was stirred at 23°C for 24 hours to obtain a polyrotaxane in which the cyclic molecules were crosslinked. After isolation, 600.0g of xylene, 250.0g of styrene, 75.0g of methyl methacrylate, and 1.5g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 5 hours while rotating the stirrer and maintaining the temperature at 90°C to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane B2 in which cyclodextrin molecules were chemically bonded to each other and side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure were bonded to the cyclodextrin.

[0128] <Preparation of Polyrotaxane B3> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred. 10.0g of the above polyrotaxane 2 ·1.0N-NaOH aqueous solution 40mL 1,4-Butanediol diglycidyl ether (Tokyo Chemical Industry Co., Ltd.) 1.2 mL The mixture was stirred at 23°C for 24 hours to obtain a polyrotaxane in which the cyclic molecules were crosslinked. After isolation, 600.0g of xylene, 300.0g of styrene, 100.0g of methyl methacrylate, and 1.5g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 8 hours while rotating the stirrer and maintaining the temperature at 90°C to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane B3 in which cyclodextrin molecules were chemically bonded to each other and side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure were bonded to the cyclodextrin.

[0129] <Preparation of Polyrotaxane B4> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred. Methacrylic acid 5.0g Methyl methacrylate 45.0g Styrene 150.0g 600.0g xylene t-Butyl peroxypivalate 1.5g The above was reacted at a temperature of 60° C. for 24 hours to obtain polymer 1. Next, after distilling off the solvent, 10.0 g of the above polyrotaxane 2 and 40 mL of concentrated sulfuric acid (98% by mass) were added thereto and stirred uniformly. Next, the mixture was stirred at a temperature of 100° C. for 1 hour to obtain a polyrotaxane in which the hydroxyl group of the cyclic molecule was ester-bonded to the carboxyl group in polymer 1.

[0130] After isolation, 600.0 g of xylene, 300.0 g of styrene, 100.0 g of methyl methacrylate, and 1.5 g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 8 hours while rotating the stirrer and maintaining the temperature at 90°C to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane B4, in which side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure are bonded to cyclodextrin.

[0131] <Preparation of Polyrotaxane B5> In a reaction vessel equipped with a stirrer, a condenser, and a thermometer, 600.0 g of xylene, 10.0 g of the above polyrotaxane 2, 150.0 g of styrene, 50.0 g of methyl methacrylate, and 1.5 g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 3 hours while rotating the stirrer and maintaining the temperature at 90°C to obtain a reaction product. The reaction product obtained was washed and dried to obtain polyrotaxane B5, in which side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure are bonded to cyclodextrin.

[0132] <Preparation of Polyrotaxane B6> To a reaction vessel equipped with a stirrer, condenser, and thermometer were added the following materials: 600.0g xylene 10.0g of the following polyrotaxane 3 (Polyrotaxane 3: SeRM Super Polymer SH1310P (product name), manufactured by ASM. The chain molecule has a polyethylene glycol structure and an adamantyl group at the end of the chain molecule, and contains, as a cyclic molecule, a plurality of α-cyclodextrins having a polycaprolactone structure in the side chain. In addition, the side chain has a hydroxyl group at the end.) Epoxy modified silicone resin (ES1001N; Shin-Etsu Chemical Co., Ltd.) 15.0 g. The temperature was maintained at 60°C while rotating the stirrer to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane B6, in which side chains having a polycaprolactone structure and a silicone polymer structure are bonded to cyclodextrin.

[0133] <Polyrotaxane B7> Polyrotaxane B7 was prepared using the above-mentioned polyrotaxane 2.

[0134] <Preparation of polyrotaxane B8> To a reaction vessel equipped with a stirrer, condenser, and thermometer were added the following materials: Xylene 1200.0g 10.0g of the above polyrotaxane 2 Styrene 1000.0g Methyl methacrylate 350.0g t-Butyl peroxypivalate 1.5g Next, polymerization was carried out for 24 hours while rotating the stirrer and maintaining the temperature at 90°C, obtaining a reaction product. The reaction product was washed and dried to obtain polyrotaxane B8, in which side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure are bonded to cyclodextrin.

[0135] <Polyrotaxane B9> As the polyrotaxane B9, the above polyrotaxane 3 was used.

[0136] <Preparation of polyrotaxane B10> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred. Xylene 1200.0g 10.0g of the above polyrotaxane 2 Styrene 1000.0g Methyl methacrylate 500.0g t-Butyl peroxypivalate 1.5g The temperature was maintained at 90°C while rotating the stirrer, and polymerization was carried out for 24 hours to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane B10, in which side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure are bonded to cyclodextrin.

[0137] <Preparation of polyrotaxane B11> In 100 mL of pure water, add 2,2,6,6-tetramethyl-1-piperidinedioxy radical (TEMPO) (6.4 × 10 -4 mol) was added, and the pH was adjusted to 10 to 11. The following materials were added to this solution and stirred at room temperature for 10 to 15 minutes to oxidize the ends of the polyethylene glycol. Sodium bromide 9.7×10 -4 Mol 10mL of 13% sodium hypochlorite solution Polyethylene glycol (Aldrich) n=35,000 7.0×10 -4 Mol Then, 10 ml of ethanol was added, the pH was adjusted to 2, and dichloromethane extraction was performed three times using 100 ml of dichloromethane.

[0138] The dichloromethane extract was evaporated to dryness under reduced pressure, dissolved in ethanol at 40-50°C, frozen for one day and night, and then polyethylene glycol with a carboxylic acid terminal (hereinafter referred to as PEG-COOH) was collected by centrifugation. The obtained PEG-COOH was freeze-dried.

[0139] The resulting PEG-COOH was dissolved in 8.6 × 10 -5mol and 1.2 × 10 α-cyclodextrin -2 mol was dissolved in 100 mL of pure water and allowed to stand in a freezer overnight. The resulting white paste-like compound was then freeze-dried to obtain a powdered inclusion complex.

[0140] The following materials were dissolved in 100 mL of anhydrous dimethylformamide and reacted at 4° C. for 24 hours. Obtained inclusion complex: 14 g Adamantaneamine 1.1×10 -3 Mol Benzotriazol-1-yloxy-tris(dimethylamino)phosphonium salt 1.1×10 -3 Mol Ethylisopropylamine 1.2×10 -3 Mol Thereafter, the mixture was washed twice with a dimethylformamide / methanol solution (1:1, v / v) and methanol, and then further washed with a mixed solution of 80 mL of anhydrous dimethyl sulfoxide and 800 mL of pure water, followed by freeze-drying to obtain polyrotaxane B11 in which α-cyclodextrin was encapsulated.

[0141] <Preparation of Coating Resin 1> The materials shown below were added to a four-neck flask equipped with a reflux condenser, thermometer, nitrogen inlet, and ground-type stirrer. Cyclohexyl methacrylate 74.5 parts by mass Methyl methacrylate 0.5 parts by mass Methacrylic acid macromonomer: 25 parts by weight (A macromonomer with a weight-average molecular weight of 5000 and a methacryloyl group at one end) Further, 100 parts by mass of toluene, 100 parts by mass of methyl ethyl ketone, and 2.0 parts by mass of azobisisovaleronitrile were added. The obtained mixture was kept at a temperature of 70°C for 10 hours under a nitrogen gas flow, and after the polymerization reaction was completed, washing was repeated to obtain a coating resin 1 solution (solid content 35% by mass). The SP value (SPa) of the coating resin 1 was 10.2 (J / cm 3 ) 1 / 2 It was.

[0142] <Preparation of Coating Resin 2> The coating resin 2 was prepared by distilling off the solvent from a silicone resin (KR242A (solid content 50%) manufactured by Shin-Etsu Chemical Co., Ltd.). The SP value (SPa) of the coating resin 2 was 8.1 (J / cm 3 ) 1 / 2 It was.

[0143] <Example 1> [Example of coating resin solution production] Coating resin 1 9.80 parts by weight Toluene 60.00 parts by weight Methyl ethyl ketone 30.00 parts by weight Polyrotaxane B1 0.20 parts by weight The above materials were dispersed for 1 hour using zirconia beads with a diameter of 0.5 mm in a paint shaker. The resulting dispersion was filtered through a 5.0 μm membrane filter to obtain a coating resin solution.

[0144] [Resin coating process] The magnetic core particles and the coating resin solution were added to a vacuum degassing kneader maintained at room temperature (the amount of the coating resin solution added was 2.5 parts of the coating resin 1 for 100 parts of the magnetic core particles 1). After addition, the mixture was stirred at a rotation speed of 30 rpm for 15 minutes, and after a certain amount of the solvent (80 mass%) had evaporated, the mixture was heated to 80°C while mixing under reduced pressure, and the toluene was distilled off over 2 hours, after which it was cooled. The magnetic carrier obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 70 μm, and then classified with a wind classifier to obtain magnetic carrier 1 having a 50% particle size (D50) of 38 μm based on volume distribution.

[0145] <Example of manufacturing two-component developer> The above toner 1 and magnetic carrier 1 were mixed in a V-type mixer (product name: V-10 type, Tokuju Seisakusho) for 0.5 seconds so that the toner concentration became 9% by mass. -1 and 5 minutes to obtain a two-component developer.

[0146] <Example of manufacturing replenishment developer> The above toner 1 and magnetic carrier 1 were mixed for 0.5 seconds using a V-type mixer (product name: V-10 type, Tokuju Manufacturing Co., Ltd.) so that the toner concentration became 90% by mass. -1 The mixture was mixed for 5 minutes to obtain a replenishment developer.

[0147] <Evaluation> The following evaluations were carried out using the obtained two-component developer and replenishment developer. First, a modified full-color copier (product name: imagePRESS C10000VP, manufactured by Canon Inc.) was used as the image forming apparatus, and two-component developer 1 was placed in the developing device of the cyan station. The copier was modified so that the developing bias could be adjusted.

[0148] Using the above-mentioned device, an image output durability test of 30,000 sheets was conducted in a normal temperature and low humidity environment (23°C / 5% RH, hereafter referred to as N / L environment) and in a high temperature and high humidity environment (30°C / 80% RH, hereafter referred to as H / H environment), and the following evaluations were conducted before and after this image output durability test.

[0149] During the durability test, the paper was passed through under the same developing and transferring conditions as the first sheet (but without calibration). The print ratio of the output image was 30%, and the developing bias was adjusted so that the initial image density was 1.55. The paper used for evaluation was A4-size plain paper for copying (product name: CF-C081, basis weight: 81.4 g / m 2 , Canon Marketing Japan) was used.

[0150] In addition, when forming an image, the developer in the cyan developing device was replaced with the above-mentioned two-component developer, and the developer in the cyan refill developer container was replaced with the above-mentioned refill developer. The reason why the two-component developer and the refill developer are used in this evaluation is because using both of them is a normal mode when using the above-mentioned image forming apparatus.

[0151] <Evaluation of image density> After the durability test in the N / L environment, three solid images were printed on the entire surface of A3 size paper. For the third image, the density of the printed image was measured at five points using an X-Rite spectrodensitometer (product name: 500 series), and the average value of the five points was taken as the image density after durability. The image density was evaluated based on the maintenance rate of the image density after durability relative to the initial image density of 1.55. The results are shown in Table 3.

[0152] It is believed that the greater the image density retention rate, the smaller the change in the chargeability of the carrier. Therefore, an image density retention rate of 70% or more was determined to be one in which the effects of the present disclosure were obtained.

[0153] <Evaluation of fogging> The following evaluations were carried out before and after the durability test in the above H / H environment.

[0154] Ten 00h images were output, and the average reflectance Dr (%) of the image area on the tenth sheet of paper was measured using a reflectometer (Tokyo Denshoku's "REFLECTOMETER MODEL TC-6DS"). The same measurement was also performed on the non-image area to measure the average reflectance Ds (%) on the paper. The above Dr (%) and Ds (%) were then substituted into the following formula to calculate the fog (%). The results are shown in Table 3. Those for which the calculated value was 1.5% or less both before and after the durability test were determined to have the effects of the present disclosure. Fog(%)=Dr(%)-Ds(%)

[0155] <Examples 2 to 17 and Comparative Example 1> In Example 1, except that the type and number of materials were changed as shown in Table 1, the same operation was carried out to obtain magnetic carriers 2 to 18, and then two-component developers and replenishment developers were similarly produced and evaluated using them. The evaluation results are shown in Table 2.

[0156] [Table 1]

[0157] In Table 1, MEK is methyl ethyl ketone. The molecular weight of the cyclic molecule is a value measured by the method described above, and the various SP values ​​are values ​​calculated by the method described above.

[0158] [Table 2]

Claims

1. A magnetic carrier having a magnetic core particle and a resin layer covering the surface of the magnetic core particle, the resin layer contains a resin and a polyrotaxane, The polyrotaxane is (i) a plurality of cyclic molecules; (ii) a chain molecule that is pierced and included in the ring of the cyclic molecule; having (iii) the chain molecule has two or more blocking groups that prevent the cyclic molecule from being detached from the chain molecule; A magnetic carrier comprising:

2. 2. The magnetic carrier according to claim 1, wherein the cyclic molecule is a molecule having a cyclodextrin skeleton.

3. 3. The magnetic carrier according to claim 2, wherein the molecule having a cyclodextrin skeleton has a weight average molecular weight of 1,000 to 50,000.

4. 4. The magnetic carrier according to claim 2, wherein the molecule having a cyclodextrin skeleton comprises a cyclodextrin and a side chain bonded to the cyclodextrin.

5. 5. The magnetic carrier according to claim 4, wherein the side chain has a polyester structure or a vinyl polymer structure.

6. 6. The magnetic carrier according to claim 5, wherein the polyester structure is a polycaprolactone structure.

7. 7. The magnetic carrier according to claim 1, wherein the content of the polyrotaxane is from 0.2% by mass to 30.0% by mass with respect to the mass of the resin.

8. the polyrotaxane comprises a first polyrotaxane and a second polyrotaxane, the resin layer contains a bound polyrotaxane formed by binding the first polyrotaxane and the second polyrotaxane, The magnetic carrier according to any one of claims 1 to 7, wherein the first polyrotaxane and the second polyrotaxane are bonded by a chemical bond between a cyclic molecule possessed by the first polyrotaxane and a cyclic molecule possessed by the second polyrotaxane.

9. the cyclic molecule is a molecule having a cyclodextrin skeleton, The weight average molecular weight of the molecule having a cyclodextrin skeleton is 1,000 to 50,000; The molecule having a cyclodextrin skeleton has a cyclodextrin and a side chain bonded to the cyclodextrin, The resin contains resin A, The ratio of the mass of the resin A to the total mass of the resin contained in the resin layer is 50 mass% or more, The SP value of the resin A is SPa (J / cm 3 ) 1/2 year, The SP value of the side chain is SPb (J / cm 3 ) 1/2 When 9. The magnetic carrier according to claim 1, which satisfies the following formula (1): |SPb-SPa|≦2.0(J / cm 3 ) 1/2 ・・・ (1)

10. 10. The magnetic carrier according to claim 9, wherein the resin A is at least one selected from the group consisting of an acrylic resin, a polyester resin, a fluororesin, and a silicone resin.

11. 11. The magnetic carrier according to claim 1, wherein the chain molecule is a molecule having a polyalkylene glycol chain.

12. 12. The magnetic carrier according to claim 1, wherein the ratio of the mass of the resin to the mass of the magnetic core particles is 1.0 to 5.0% by mass.

13. A two-component developer containing a toner and a magnetic carrier, The magnetic carrier is the magnetic carrier according to any one of claims 1 to 12. A two-component developer comprising:

14. A replenishment developer containing a toner and a magnetic carrier, The magnetic carrier is the magnetic carrier according to any one of claims 1 to 12. A replenishing developer comprising:

Citation Information

Patent Citations

  • Carrier for electrostatic charge image development, electrostatic charge image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method

    JP2016170216A

  • Temperature responsive polyrotaxane gel and drug carrier

    JP2017031258A

  • Compound comprising crosslinked polyrotaxane

    WO2001083566A1